Labor Market Effects of the German Tax Reform 2000 - Peter Haan; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
In the year 2000, the German government passed the most ambitious tax reform in postwar German history aiming at a significant tax relief for households. An important aim of this tax reform was to improve work incentives and, thereby, foster employment. Drawing on data of the German Socio Economic Panel (SOEP), we analyze the work incentive and employment effects of this reform on the basis of a behavioral microsimulation model. We find that the significant reduction of marginal tax rates implied by the tax reform results in a substantial increase in labor supply, a slight reduction of market wages and an increase in employment of about 130 thousand people (full-time equivalents).
Keywords: J22; H31; H24; 330; tax reform; behavioral effects; labor market effects; Einkommensteuer; Steuerreform; Steuerwirkung; Arbeitsangebot; Beschäftigungseffekt; Schätzung; Deutschland